(untitled) (Educação e Pesquisa, 2015)
This article presents a reflective and dialogical approach to evaluation that has been developed over twenty years by an educational research group at the University of Pavia and has been tested in the field in various experiences and research conducted in Italy in which day-care center and nursery school educators were directly involved. The approach, inspired by Guba and Lincoln’s fourth generation evaluation and Dewey’s theory of reflective thinking, considers evaluation as a process by which people working in an educational institution can reflect in groups on their educational beliefs and practices in order to plan and implement improvement actions. After briefly outlining the main characteristics of the approach, I will focus on the role played in it by a facilitator, a figure from outside the educational reality object of evaluation whose principal task is to help the participants to reconstruct a shared image of the reality in which they operate, making it possible to envisage the future, to think about why you do what you do and how you could improve it. The principal goal of this figure is to “promote from within” soliciting the empowerment of groups of educators and teachers through reflection. On the basis of a recent research, the communicative and maieutic strategies performed by this figure in promoting processes of self-evaluation in groups of educators and teachers will be presented.